A monograph and re-classification of the previous genus Limosina Macquart (Diptera, Sphaeroceridae) of Europe. Part II. - Roháček, Jindřich (Contributions to Entomology = Beiträge zur Entomologie, 1983)
The European species belonging to the previous genus Limosina Macquart (sensu Hackmann 1969a) are monographed. This taxon was found to be polyphyletic and is divided using cladistic classification into 17 genera with a total of 81 European species. 11 genera and 11 subgenera are discribed as new: Gigalimosina gen. nov., Herniosina gen. nov., Terrilimosina gen. nov., Minilimosina gen. nov., Minilimosina (Svarciella) subgen. nov., Minilimosina (Allolimosina) subgen. nov., Xenolimosina gen. nov., Paralimosina (Canarisina) subgen. nov., Spelobia (Eulimosina) subgen. nov., Spelobia (Bifronsina) subgen. nov., Pullimosina gen. nov., Pullimosina (Dahlimosina) subgen. nov., Spinilimosina gen. nov., Kimosina gen. nov., Kimosina (Kollimosina) subgen. nov., Kimosina (Alimosina) subgen. nov., Telomerina gen. nov., Opalimosina gen. nov., Opalimosina (Pappiella) subgen. nov., Opalimosina (Hakmanina) subgen. nov., Opalimosina (Dentilimosina) subgen. nov., and Rudolfia gen. nov. Other included (Limosina Maquart, 1835; Apteromyia Vimmer, 1929 gen. restit.; Paralimosina Papp, 1973; Spelobia Spuler, 1924 nom. restit., stat. nov.; Chaetopodella Duba, 1920; Halidayina Duba 1918) are rediscribed. Descriptions of 14 new species are given (Minilimosina 4, Spelobia 6, Kimosina 1, Telomeina 3), other are fully rediscribed. 4 new synonyms are established; numerous species (besides those included in the Monograph) are put in new combinations. All available type material of European species (including synonyms) was revised, number of lectotypes designated and in this way the status of particular species fixed. A description of each species is supplemented by numerous illustrations, data on the morphology of preimaginal stages, biology, distribution and by discussion of relationships. Identification keys to all included taxa are given. The general part includes a summary of basic data dealing with history of investigations, morphology, biology, zoogeography and phylogeny (cladistic classification) of the groups under study. Nomenclatural Acts claviventris (Strobl, 1909) (Apteromyia), comb. no. hitherto Limosina claviventris flaviceps (Zetterstedt, 1847) (Gigalimosina), comb. n. hitherto Limosina flaviceps bequaerti (Villeneuve, 1917) (Herniosina), comb. n. hitherto Leptocera (Limosina) bequaerti horrida (Roháček, 1978) (Herniosina), comb. n. hitherto Limosina horrida Alimosina Roháček, 1983 (Kimosina), sgen. n. Collimosina Roháček, 1983 (Kimosina), sgen. n. empirica (Hutton, 1901) (Kimosina (Alimosina)), comb. n. hitherto Borborus empiricus spinosa (Collin, 1930) (Kimosina (Collimosina)), comb. n. hitherto Limosina spinosa ciliata (Duda, 1918) (Kimosina (Kimosina)), comb. n. hitherto Limosina (Scotophilella) ciliata glabrescens (Villeneuve, 1917) (Kimosina (Kimosina)), comb. n. hitherto Leptocera (Limosina) glabrescens longisetosa (Dahl, 1909) (Kimosina (Kimosina)), comb. n. hitherto Limosina longisetosa pappi Roháček, 1983 (Kimosina (Kimosina)), spec. n. plumosula (Rondani, 1880) (Kimosina (Kimosina)), comb. n. hitherto Limosina plumosula latigena Roháček, 1977 (Limosina), syn. n. of Paralimosina (Paralimosina) kaszabi Papp, 1973 Allolimosina Roháček, 1983 (Minilimosina), sgen. n. Svarciella Roháček, 1983 (Minilimosina), sgen. n. albinervis (Duda, 1918) (Minilimosina (Allolimosina)), comb. n. hitherto Limosina (Scatophilella) albinervis alloneura (Richards, 1952) (Minilimosina (Allolimosina)), comb. n. hitherto Leptocedra (Limosina) alloneura secundaria (Duda, 1918) (Minilimosina (Allolimosina)), comb. n. hitherto Limosina (Scatophilella) secundaria fungicola (Haliday, 1836) (Minilimosina (Minilimosina)), comb. n. hitherto Limosina fungicola gemella Roháček, 1983 (Minilimosina (Minilimosina)), spec. n. parvula (Stenhammar, 1854) (Minilimosina (Minilimosina)), comb. n. hitherto Limosina parvula tenera Roháček, 1983 (Minilimosina (Minilimosina)), spec. n. trogeri Roháček, 1983 (Minilimosina (Minilimosina)), spec. n. hackmani (Roháček, 1977) (Minilimosina (Svarciella)), comb. n. hitherto Limosina hackmani ismayi Roháček, 1983 (Minilimosina (Svarciella)), spec. n. splendens (Duda, 1928) (Minilimosina (Svarciella)), comb. n. hitherto Limosina (Scotophilella) splendens v-atrum (Villeneuve, 1917) (Minilimosina (Svarciella)), comb. n. hitherto Leptocera (Limosina) v-atrum vitripennis (Zetterstedt, 1847) (Minilimosina (Svarciella)), comb. n. hitherto Limosina vitripennis Dentilimosina Roháček, 1983 (Opalimosina), sgen. n. Hackmanina Roháček, 1983 (Opalimosina), sgen. n. Pappiella Roháček, 1983 (Opalimosina), sgen. n. denticulata (Duda, 1924) (Opalimosina (Dentilimosina)), comb. n. hitherto Limosina (Scotophilella) czernyi (Duda, 1918) (Opalimosina (Hackmanina)), comb. n. hitherto Limosina (Scotophilella) czernyi calcarifera (Roháček, 1975) (Opalimosina (Opalimosina)), comb. n. hitherto Limosina calcarifera collini (Richards, 1929) (Opalimosina (Opalimosina)), comb. n. hitherto Leptocera collini mirabilis (Collin, 1902) (Opalimosina (Opalimosina)), comb. n. hitherto Limosina mirabilis simplex (Richards, 1929) (Opalimosina (Opalimosina)), comb. n. hitherto Leptocera grenstedi var. simplex liliputana (Rondani, 1880) (Opalimosina (Pappiella)), comb. n. hitherto Limosina liliputana Canarisina Roháček, 1983 (Paralimosina), sgen. n. beckeri (Duda, 1918) (Paralimosina (Canarisina)), comb. n. hitherto Limosina (Scotophilella) beckeri fucata (Rondani, 1880) (Paralimosina (Paralimosina)), comb. n. hitherto Limosina fucata macedonica (Roháček, 1977) (Paralimosina (Paralimosina)), comb. n. hitherto Limosina macedonica subcribrata (Roháček, 1977) (Paralimosina (Paralimosina)), comb. n. hitherto Limosina subcribata trichopyga (Richards, 1952) (Paralimosina (Paralimosina)), comb. n. hitherto Leptocera (Limosina) trichopyga Dahlimosina Roháček, 1983 (Pullimosina), sgen. n. dahli (Duda, 1918) (Pullimosina (Dahlimosina)), comb. n. hitherto Limosina (Scotophilella) dahli karelica (Papp, 1979) (Pullimosina (Dahlimosina)), comb. n. hitherto Limosina karelica antennata (Duda, 1918) (Pullimosina (Pullimosina)), comb. n. hitherto Limosina (Scotophilella) antennata heteroneura (Haliday, 1836) (Pullimosina (Pullimosina)), comb. n. hitherto Limosina heteroneura meijerei (Duda, 1918) (Pullimosina (Pullimosina)), comb. n. hitherto Limosina (Scotophilella) meijerei moesta (Villeneuve, 1918) (Pullimosina (Pullimosina)), comb. n. hitherto Limosina (Leptocera) moesta pullula (Zetterstedt, 1847) (Pullimosina (Pullimosina)), comb. n. hitherto Limosina pullula rozkosnyi (Roháček, 1975) (Rudolfia), comb. n. hitherto Limosina rozkosnyi Bifronsina Roháček, 1983 (Spelobia), sgen. n. Eulimosina Roháček, 1983 (Spelobia), sgen. n. bifrons (Stenhammar, 1854) (Spelobia (Bifronsina)), comb. n. hitherto Limosina bifrons ochripes (Meigen, 1830) (Spelobia (Eulimosina)), comb. n. hitherto Borborus ochripes baezi (Papp, 1977) (Spelobia (Spelobia)), comb. n. hitherto Limosina baezi belanica Roháček, 1983 (Spelobia (Spelobia)), spec. n. cambrica (Richards, 1929) (Spelobia (Spelobia)), comb. n. hitherto Leptocera cambrica clunipes (Meigen, 1830) (Spelobia (Spelobia)), comb. n. hitherto Borborus clunipes czizeki (Duda, 1918) (Spelobia (Spelobia)), comb. n. hitherto Limosina (Scotophilella) czizeki faeroensis (Deeming, 1966) (Spelobia (Spelobia)), comb. n. hitherto Leptocera (Limosina) faeroensis ibrida Roháček, 1983 (Spelobia (Spelobia)), spec. n. luteilabris (Rondani, 1880) (Spelobia (Spelobia)), comb. n. hitherto Limosina luteilabris manicata (Richards, 1927) (Spelobia (Spelobia)), comb. n. hitherto Limosina manicata nana (Rondani, 1880) (Spelobia (Spelobia)), comb. n. hitherto Limosina nana palmata (Richards, 1927) (Spelobia (Spelobia)), comb. n. hitherto Limosina palmata pappi Roháček, 1983 (Spelobia (Spelobia)), spec. n. parapusio (Dahl, 1909) (Spelobia (Spelobia)), comb. n. hitherto Limosina parapusio pseudonivalis (Dahl, 1909) (Spelobia (Spelobia)), comb. n. hitherto Limosina pseudonivalis pseudosetaria (Duda, 1918) (Spelobia (Spelobia)), comb. n. hitherto Limosina (Scotophilella) pseudosetaria quaesita Roháček, 1983 (Spelobia (Spelobia)), spec. n. rufilabris (Stenhammar, 1854) (Spelobia (Spelobia)), comb. n. Limosina simplicipes (Duda, 1925) (Spelobia (Spelobia)), comb. n. hitherto Limosina (Scotophilella) simplicipes talis Roháček, 1983 (Spelobia (Spelobia)), spec. n. talparum (Richards, 1927) (Spelobia (Spelobia)), comb. n. hitherto Limosina taplarum ulla Roháček, 1983 (Spelobia (Spelobia)), spec. n. villosa (Duda, 1918) (Spelobia (Spelobia)), comb. n. hitherto Limosina (Scotophilella) villosa Aptilomyia Vimmer, 1929 (Sphaeroceridae), syn. n. of Apteromyia Vimmer, 1929 Gigalimosina Rohácek, 1983 (Sphaeroceridae), gen. n. Herniosina Rohácek, 1983 (Sphaeroceridae), gen. n. Kimosina Roháček, 1983 (Sphaeroceridae), gen. n. Minilimosina Roháček, 1983 (Sphaeroceridae), gen. n. Opalimosina Roháček, 1983 (Sphaeroceridae), gen. n. Pullimosina Roháček, 1983 (Sphaeroceridae), gen. n. Rudolfia Roháček, 1983 (Sphaeroceridae), gen. n. Spelobia Spuler, 1924 (Sphaeroceridae), stat. n. hitherto subgenus of Leptocera Spinilimosina Roháček, 1983 (Sphaeroceridae), gen. n. Telomerina Roháček, 1983 (Sphaeroceridae), gen. n. Terrilimosina Roháček, 1983 (Sphaeroceridae), gen. n. Vseteckiella Vimmer, 1931 (Sphaeroceridae), syn. n. of Apteromyia Vimmer, 1929 Xenolimosina Roháček, 1983 (Sphaeroceridae), gen. n. brevicostata (Duda, 1918) (Spinilimosina), comb. n. hitherto Limosina (Scotophilella) brevicostata antonini Roháček, 1983 (Telomerina), spec. n. eburnea Roháček, 1983 (Telomerina), spec. n. flavipes (Meigen, 1930) (Telomerina), comb. n. hitherto Borborus flavipes pseudoleucoptera (Duda, 1924) (Telomerina), comb. n. hitherto Limosina (Scotophilella) pseudoleucoptera ursina Roháček, 1983 (Telomerina), spec. n. racovitzai (Bezzi, 1911) (Terrilimosina), comb. n. hitherto Limosina racovitzai schmitzi (Duda, 1918) (Terrilimosina), comb. n. hitherto Limosina (Scotophilella) schmitzi sudetica (Roháček, 1975) (Terrilimosina), comb. n. hitherto Limosina sudetica setaria (Villeneuve, 1918) (Xenolimosina), comb. n. hitherto Limosina (Leptocera) setaria